Bespoke flow experiments to capture the dynamics of coughs and sneezes. (6th September 2021) - de Silva, Charitha M; Bahl, Prateek; Doolan, Con; Raina MacIntyre, C
Abstract: Here, we detail and analyse a set of tailored experiments to capture the flow dynamics of coughs and sneezes. Specifically, conventional particle tracking-based flow experiments are tailored to capture the wide range of spatial and temporal scales in the flow through the use of high-speed and high-resolution imaging systems. In doing so, we captured droplet velocities over a wide range of particle sizes with a large field-of-view in the order of a metre to capture the full flow field, which is challenging to achieve through conventional methods. A simultaneous direct measure of droplet sizing and velocity is also obtained through back-illuminated imaging experiments, albeit over a smaller spatial extent. A statistical assessment of the droplets' flow-field reveals good agreement to prior works, now extending this over a much larger spatial extent. Through a statistical analysis of representative sneeze and cough samples, we highlight the potential of the presented experimental techniques to provide detailed flow dynamics. In particular, we observe that droplets are expelled over a significantly shorter period than the airflow generated in a cough; in contrast, droplets appear to be continuously expelled during the span of a sneeze. Furthermore, due to the lower momentum in coughs, droplets exhibit aerosolised behaviour at an earlier stage than sneezes, where the stronger flow-field expelled dictates the droplet dynamics through the bulk of the sneeze duration. These findings reveal crucial differences between coughs and sneezes, which are essential when modelling such flow accurately or designing pressure-driven simulators.